Spiritual Group Counseling: An Overview of the Gestalt Approach in Handling Imitation Behavior - Asep Solikin; Muhammad Andi Setiawan; Karyanti Karyanti; Khairunnisa Khairunnisa (Jurnal Konseling dan Pendidikan, 2022)
Negative-imitation behavior follows a behavior that they feel is acceptable, and it becomes a common thing for students to imitate and sometimes becomes a habit. Also, the habits learned from their parents, and the environment makes them a person who follows the climate as they are around. Without realizing it, negative imitation will have a negative impact, sometimes even contrary to existing norms. With that, the Gestalt Spiritual group counseling service is expected to understand and realize that the behavior they imitate is wrong. The research method used is a pre-experiment that will be used to determine whether there is any influence in gestalt spiritual group counseling. The research sample consisted of sixteen people who were divided into two groups of guidance. The research results obtained after the experiment was carried out, namely that there were changes for students' better. The SPSS analysis carried out showed a decrease in negative-imitation behavior in students